The impact of board diversity and sustainability engagement on bank performance - Aureli, Selena; Brighi, Paola; Schadewitz, Hannu (Springer Science and Business Media LLC, 2026)
Today’s organizations face unprecedented challenges related to societal and environmental matters. The long-term trends related to climate change are expected to generate instability in the credit market and negatively affect organizational performance. Organizations can mitigate these issues and better grasp different trends by having a diverse board (i.e., board members of different genders, ages, qualifications and nationalities). However, that same diversity may also create conflicts and worsen strategic decision-making. Grounded on stakeholder theory, this study investigates the impact of board diversity on bank performance, assuming that board diversity also shapes environmental, social, and governance (ESG) engagement, which is linked to financial performance. Our data comprises a sample of public commercial banks located in OECD countries. The results suggest that board diversity (as a bundle of different traits and characteristics) contributes positively to performance. However, the impact measured by the means of accounting-based and market-based performance measures differs. In addition, we found that ESG investments adversely affect profitability ratios, but a more diverse board mitigates the possible detrimental effects of ESG expenses on company returns. By helping to illuminate the short- and long-term effects of board diversity on bank performance, the results hold value for regulators, policymakers, supervisory authorities, banks, and managers.